An Analysis of the Methods for Teaching English to Beginners at the Extension Program of Foreign Languages at the Western Multidisciplinary Campus of the University of El Salvador - Villatoro Guevara, Rosa Elvira; Guerra López, Sandra Yanira (2024)
This thesis comprises significant information about the research project “An Analysis of the Methods for Teaching English to Beginners at the Extension Program of Foreign Languages at the Western Multidisciplinary Campus of the University of El Salvador” carried out from April, 4, 2006 to November 15, 2006.